Distributed Secure Economic Dispatch Strategy Based on Robust Graph Theory and W-MSR Algorithm - Jian Le; Jing Wang; Hongke Lang; Weihao Wang (Sensors)
The traditional consensus-based distributed economic dispatch strategy may lose system convergency and cause imbalanced power when facing an information attack on the individual power generation unit; thus, it is unable to achieve the dispatching goal. Taking into consideration several kinds of attack behaviors that may exist in a distributed control system, this paper develops models of node attacks from the two aspects of action mode and deployment scope, and analyzes the influence of attack behaviors on the distributed economic dispatch system. Based on the idea of the W-MSR algorithm that deletes the information received from nodes that may be attacked, a distributed security consensus-based economic dispatch strategy is synthetized with the incremental cost of the power generation unit as the consensus variable. Based on the graph robustness index, this paper gives its conditions along with its proof that the communication network topology of the system should be satisfied when adopting the W-MSR algorithm. The simulation results of the IEEE-39 bus distribution network show that the strategy proposed in this paper can effectively counter various information attacks, enhancing both the security and economic efficiency of the distributed economic dispatch system. In addition, the (F + 1, F + 1)-robust graph is a necessary and sufficient condition to achieve the consensus of the dispatch strategy.